Expenditure Ceilings-A Survey - Ljungman, Gosta (Washington, D.C. : International Monetary Fund, 2008)
This paper looks at the factors that have to be considered when designing an aggregate expenditure ceiling. It is argued that expenditure ceilings are effective in promoting fiscal discipline and sustainability, but that a number of trade-offs have to be made when setting up a fiscal framework that will survive in a politically charged environment. The paper illustrates the discussion with a case study of medium-term aggregate expenditure ceilings in three countries: Finland, the Netherlands and Sweden.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet